2017
DOI: 10.1007/s00464-017-5471-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stent dysfunction after self-expandable metal stent placement for malignant gastric outlet obstruction: tumor ingrowth in uncovered stents and migration of covered stents

Abstract: Both U-SEMS and C-SEMS are effective with comparable patencies. Tumor ingrowth and stent migration are the main causes of stent dysfunction for U-SEMS and C-SEMS, respectively. With regard to stent dysfunction, U-SEMS might be a good option for patients receiving chemotherapy, while C-SEMS with longer stents for patients in good condition. (Clinical trial registration number: UMIN000024059).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
2
21
1
1
Order By: Relevance
“…On the other hand, a gastrojejunostomy, even if it is a palliative operation, might give the feeling to have done something more with respect to SEMS positioning. Consequently, SEMS permits a rapid return to oral feeding as also reported in the recent literature [ 2 , 6 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and confirmed by our investigation, thus accelerating the discharge of the patients from hospital and improving their return to a normal life. Furthermore, Ly J. et al [ 29 ], in a systematic review, demonstrated a higher incidence of major medical complications (respiratory tract infection, myocardial infarction, and acute renal failure) in patients who underwent surgery for palliation of malignant GOOS when compared to SEMS positioning.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, a gastrojejunostomy, even if it is a palliative operation, might give the feeling to have done something more with respect to SEMS positioning. Consequently, SEMS permits a rapid return to oral feeding as also reported in the recent literature [ 2 , 6 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and confirmed by our investigation, thus accelerating the discharge of the patients from hospital and improving their return to a normal life. Furthermore, Ly J. et al [ 29 ], in a systematic review, demonstrated a higher incidence of major medical complications (respiratory tract infection, myocardial infarction, and acute renal failure) in patients who underwent surgery for palliation of malignant GOOS when compared to SEMS positioning.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, duodenal U‐SEMS and C‐SEMS in patients with DS have not been compared. Duodenal U‐SEMS and C‐SEMS in patients with malignant gastric outlet obstruction did not differ in terms of their recurrent obstruction rates, overall adverse events, and times to stent dysfunction . The main causes of stent dysfunction are tumor ingrowth in U‐SEMS and stent migration in C‐SEMS .…”
Section: Discussionmentioning
confidence: 89%
“…Duodenal U-SEMS and C-SEMS in patients with malignant gastric outlet obstruction did not differ in terms of their recurrent obstruction rates, overall adverse events, and times to stent dysfunction. [40][41][42] The main causes of stent dysfunction are tumor ingrowth in U-SEMS and stent migration in C-SEMS. 41 Tumor ingrowth in U-SEMS occurs in 4% to 26% of patients with duodenal U-SEMS, 43 similar to our findings (U-SEMS vs C-SEMS: 7.7% [5/65] vs 0.0% [0/44]; P = 0.08).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duodenal covered self-expandable metal stents (C-SEMSs) are designed with stent mesh to prevent tumor ingrowth [1]. However, stent migration is a major adverse event associated with C-SEMS, occurring in 8 % -25 % of cases [2,3]. In some cases, migrated stents exit via the rectum or remain in the body without complications [4].…”
mentioning
confidence: 99%